อุปลักษณ์ในวาทกรรมการเมืองไทยในการหาเสียงเลือกตั้งสมาชิกสภาผู้แทนราษฎรเป็นการทั่วไป พ.ศ.2562: การวิเคราะห์อุปลักษณ์เชิงวิพากษ์ - นิภาดา โพธิ์เรือง (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
The 2019 general election in Thailand was marked by high political competition and attempts to divide political parties. From a preliminary study of the election campaign, it was found that Thai politicians adopted metaphors as an important method in the battle of ideas. This research therefore aims to study the conceptual metaphors reflected from the linguistic metaphors used by Thai politicians in political discourse during the 2019 general election campaign by adopting the conceptual frameworks of Conceptual Metaphor Theory, Critical Metaphor Analysis, Metaphor Scenario, and Conceptual Blending Theory. Four groups of political discourse were collected including speeches, debates, interviews, and political party songs. These data groups were published during the period between 23 January and 23 March 2019, which was designated as the election campaign.The results of the study found a total of 1,623 metaphorical expressions, classified into 17 conceptual metaphors and 34 metaphor scenarios. The most common metaphor was [POLITICS IS A JOURNEY]. The results of the metaphor analysis according to the concept of critical analytical metaphor found that politicians use metaphors to present 5 concepts that give their side legitimacy and political advantage: 1) Politicians are capable leaders or heroes. 2) Politicians are dependable, benevolent, and supportive. 3) Politicians are those with reliable knowledge. 4) Politicians are those who renovate and manage society. 5) Politicians on their side are those who have good intentions and are ready to give good things to the people. There are 4 ideas used to reduce the legitimacy of politicians on other sides: 1) Politicians on the other sides are cheaters and full of tricks and deception. 2) Politicians on other sides are incompetent. 3) Politicians from other sides are the ones who create trouble in people s lives. 4) Politicians from other sides are disgusting. In addition, 6 concepts were presented regarding Thai politics, divided into 3 concepts used to create/reduce legitimacy between political groups: 1) Democratic politics leads to conflict, so there is a need for other solutions to overcome and lead the country to overcome obstacles. 2) Changes in political power are a normal thing that can happen. 3) The old form of politics is backward, but the new form of politics is hope. There are 3 concepts used to define the relationship between politicians and the people: 1) The people are those who have power like politicians. 2) Politics is simply a matter of politicians and 3) People should obey politicians because politicians have the rightful authority to control the people.A critical observation on the use of metaphors by Thai politicians in political discourse during the 2019 general election campaign for members of the House of Representatives found that metaphors were clearly used to create legitimacy for their side and using metaphors to delegitimize other politicians, creating negative feelings towards different political ideas with exaggerated metaphors, the paradox of using metaphors to present political ideas, and has obsessive ideas hidden in political metaphors. From a critical perspective, the analysis reveals that metaphors in the political discourse were adopted as a device for the politicians to present themselves as "the right choices" and "the right ways" in order to persuade the voters and to earn them political power. In addition, the metaphor analysis indicates that according to the politicians, politics is simply the matter of the politicians and the politicians can legitimately take control over the people.